1991
DOI: 10.1051/rnd:19910607
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in plasma concentrations of gonadotropins and in the responsiveness of the pituitary and testis to GnRH in a desert rodent, the sand rat (Psammomys obesus)

Abstract: Summary ― The male sand rat (Psammomys obesus), captured alive in the Sahara desert in the area of B6ni-Abb6s (Algeria), exhibited seasonal changes in plasma concentrations of LH, characterized by an increase in early summer. Administration of a standard dose of GnRH (200 ng/100 g body weight) failed to elicit significant season-dependent changes in LH release, whereas the increase in plasma testosterone was maximum in June-July and quite small between November and March-April. The present results sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In the sand rat (Psammomys obesus), a short day breeder, plasma LH concentration increases in early summer and that intravenous administration of GnRH (200 ng/100 g of body weight) fails to elicit significant season-dependent changes in LH release, whereas the increase in plasma testosterone was maximum in June-July and low between November and March-April. The summer seasonal onset of the testicular endocrine activity of the sand rat is due to increases in both in LH release and testes sensitivity to gonadotropin [34]. Other studies showed that GnRH is involved in the regulation of pituitary gonadotropin secretion by a system that depends on frequency pulsations.…”
Section: Discussionmentioning
confidence: 99%
“…In the sand rat (Psammomys obesus), a short day breeder, plasma LH concentration increases in early summer and that intravenous administration of GnRH (200 ng/100 g of body weight) fails to elicit significant season-dependent changes in LH release, whereas the increase in plasma testosterone was maximum in June-July and low between November and March-April. The summer seasonal onset of the testicular endocrine activity of the sand rat is due to increases in both in LH release and testes sensitivity to gonadotropin [34]. Other studies showed that GnRH is involved in the regulation of pituitary gonadotropin secretion by a system that depends on frequency pulsations.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the jerboa, striking seasonal changes in GnRH expression in the POA appear to be independent of photoperiod, and also independent of both seasonal variations in food availability and environmental temperature. As concerns the sex steroids–GnRH interaction, a functional relation has been well established in mammals (29–33). Recently, evidence has been provided that the GnRH receptor mRNA is positively regulated during the morning of proestrus, probably following an increase in the level of oestradiol, in preparation for the preovulatory GnRH‐LH surge (30).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this species constituted a model for studying several metabolic disorders when confined to standard laboratory diet, Psammomys develops diabetes [22,23] and other pathology [24,25]. In the male, different studies were already published [26][27][28]. In the female, the estrous cycle was characterized [29], in the gonad the histological aspect was published [30], the histological and cytological seasonal variations of the reproductive tract were studied [31].…”
Section: Introductionmentioning
confidence: 99%